The Effect of Alpha s1 Genotype on Some Physiological and Chemical Milk Characteristics in Garganica Goat - Santillo, Antonella; Ciliberti, Maria Giovanna; d’Angelo, Francesca; Albenzio, Marzia (Frontiers in Animal Science, 2022)
In the present study individual milk samples were collected from 80 Garganica goats and the population was genotyped for CSN1S1; seven different alleles were observed with the A allele found as predominant, followed by the F and B allele. A number of 14 different genotypes were observed. A proteomic approach was used to classify the individual milk on the basis of protein abundance: four levels of αs1-casein (CN) expression were identified as high (HAS-1), intermediate (IAS-1), low (LAS-1) and null (NAS-1). The present paper aimed to investigate the influence of the level of expression of αs1-casein fraction in milk on proteolytic activities, chemical composition, and renneting properties of individual Garganica goat milk. Results from the present study evidenced that the level of expression of αs1-casein fraction in Garganica goat milk affected chemical composition, curd firmness, and indigenous proteolytic enzymes. In particular fat, protein, and casein content were higher in HAS-1 and IAS-1 compared to LAS-1 and NAS-1. The SCC decreased passing from the HAS-1 to the NAS-1, and the curd firmness displayed the highest value in HAS-1. The activity of plasmin (PL) was higher in HAS-1 and IAS-1 groups compared to the LAS-1 and NAS-1; whereas, PL plasminogen-derived (PG) activity was the highest in NAS-1 group. On the contrary, the activity of elastase was the highest in LAS-1, intermediate in the IAS-1 group, and the lowest in HAS-1 and NAS-1 groups. Present data demonstrated that the level of synthesis of αs1-CN reflects the efficiency of the mammary gland in the activation of the cellular mechanisms, and influences the proteolytic activity in milk, especially the PL-PG system.